The Response of Residents of the Building and Non-structural Components, in Contrast to Explosions at Ground Level from the Standpoint of Passive Defense - Mozaffarpour Taromi, MohammadReza; Khosravi, Hossein (Salehan Institute of Higher Education, 2019)
The research by non-military research associations and assemblies on explosion have increased due to the growth in the death and damage rates resulting from explosion, particularly blasts induced by terroristic invasions which mostly occur on the ground. Most studies are conducted with a major focus on strengthening the structures against explosions. Further, scholars have focused on resistance and ductility criteria required for the design and control over structural elements. Now, the question is whether the health of a structure can represent its inhabitants’ health. Few studies have been done on the convenience of inhabitants and response of non-structural elements, which are limited to impact of vibrations on high-rise structures caused by the loads imposed by wind and earthquake. The important factors relevant to the health and convenience of building inhabitants are as follows: speed, acceleration, and variations in the acceleration of floors.In this paper, the aforementioned parameters are measured, according to which the convenience and health of inhabitants were assessed. For this purpose, two 4-story and 8-story buildings were selected on which four selective explosions were applied. The results were then presented in two forms of maximum values and dynamic response by performing dynamic modal linear time history analysis. The building's response under typical forces such as dead and live and earthquake forces was remarkably desirable and the behavior remained linear, but the building’s acceleration may cause serious injuries in terms of human comfort criteria. The obtained results indicated that the healthy state of the structure does not represent the health of the building inhabitants. Further, although the building was safe against the elective blasts, the lateral accelerations were capable of imposing significant damages to the building residents. This can be considered as a criterion for control and future designs from a passive defense point of view, as the explosions induced by terroristic attacks is increasing.